(3GdfXGe GdbGfhfi ddYeGd GdCLGfH ai GdeedcI GdYQHjI GdSYhOjI (B/ s - (3YHOGddg Hf eMeO Hf CMeO Bd MehOs; (3CMeO MSf GdHQYis; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2019)
(3JfGhd gPG GdHMK (B((3GdfXGe GdbGfhfi ddYeGd GdCLGfH ai GdeedcI GdYQHjI GdSYhOjI(B) (3eGgjI GdYeGdI GdCLfHjI h JWhQgG h CHQR SeGJgG h Gdeaghe GdbGfhfi deOdhd GdYeGd GdCLGfH ai eYGjjQ GdYed GdOhdjI h GdYQHjI hGdJTQjY GdhWfi h HjfJ GdYhGed GdQFjSjI dfeh GdYeGdI GdCLfHjI h GdUYhHGJ GdJi JhGLggG ai HdOGf GdEQSGd h HdOGf GdGSJbHGd h GdBKGQ GdeQJHI Ydi JhGLOgG ef GdfGMjI GdSjGSjI h GdCefjI h GdGLJeGYjI h GdGbJUGOjI ceG GSJYQV GdHMK GdMeGjI GdebQQI ddYeGd GdCLGfH habkG deYGjjQ GdYed GdOhdjI h GdYQHjI h ehba GdeTQY GdSYhOi(B: (3ceG JVef GdHMK CMcGe h bhGYO JTZjd GdYeGd GdCLGfH ai GdeedcI GdYQHjI GdSYhOjI ef MjK GdJYQa Ydi fXGe GdcaGdI h dGFMI GSJbOe GdYeGdI GdhGaOI h CMcGe GdONhd h GdEbGeI HbUO GdYed(B: (3h TQhW GdJQNjU HGdYed ddCLGfH h ELQGAGJgG h LRGA eNGdaJgG(B: (3h Mbhb h GdJRGeGJ GdYeGd ai Xdi CMcGe bGfhf GdYed GdSYhOi(B: (3h NWW GdeedcI GdYQHjI GdSYhOjI ai GdMO ef GSJNOGe GdYeGd GdCLGfHs
(3jTJed Ydi edGMbs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdJTQjYGJ GdGLJeGYjI, (B2019s
(3HHdjhLQGajG(B: (3UaMGJ (B213-231s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3JTQjYGJ ELJeGYjIs; (3GdYeGd GdCLGfHs; (3Mbhb h GdJRGeGJ GdYeGd GdCLGfHs; (3fXGe GdcaGdIs; (3GdeHGOF GdebQQI dMeGjI GdYeGd GdCLGfHs; (3GdMbhb GdebQQI dMeGjI GdYeGd GdCLGfHs; (3bhGYO JTZjd GdYeGd GdCLGfH aj GdeedcI GdYQHjI GdSYhOjIs; (3Mbhb GdYeGd GdCLGfH aj GdeedcI GdYQHjI GdSYhOjIs; (3GdJRGeGJ GdYeGd GdCLGfH aj GdeedcI GdYQHjI GdSYhOjIs; (3GdMO ef GSJNOGe GdYeGd GdCLGfH aj GdeedcI GdYQHjI GdSYhOjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdJTQjYGJ GdELJeGYjIs